2016
DOI: 10.1589/jpts.28.257
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thoracic and cervical joint mobilization on pulmonary function in stroke patients

Abstract: [Purpose] This study aimed to conduct thoracic and cervical mobilization in stroke patients and determine its effects on respiratory function. [Subjects and Methods] Twenty-one stroke patients were studied. Subjects were divided into a control group (control group, n=11) who did not undergo thoracic and cervical joint mobilization, and an experimental group (thoracic and cervical mobilization group, n=10) who underwent thoracic and cervical joint mobilization. Forced vital capacity and forced expiratory volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 19 publications
(25 reference statements)
3
16
0
Order By: Relevance
“…These results indicate the importance of rib cage joint mobilization in pulmonary rehabilitation of stroke patients. These results are consistent with the results of other studies, which showed that addition of joint mobilization to conventional rehabilitation induces treatment effects on pulmonary function at which the respiratory intervention is specifically aimed [16][17][18]28].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results indicate the importance of rib cage joint mobilization in pulmonary rehabilitation of stroke patients. These results are consistent with the results of other studies, which showed that addition of joint mobilization to conventional rehabilitation induces treatment effects on pulmonary function at which the respiratory intervention is specifically aimed [16][17][18]28].…”
Section: Discussionsupporting
confidence: 92%
“…When compared with studies regarding the effects of joint mobilization and manual therapy applied to the spine on respiratory function [18,19,28], the present study showed a wider range of therapeutic effects of rib cage joint mobilization such as improved chest expansion, inspiratory muscle activity, and pulmonary function.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The decrease of elastic properties of cells causes emphysema, imbalance of ventilation-perfusion, decrease of surface area per lung volume, and in turn, dyspnea. In addition, as aging progresses, osteoporosis of the ribs, calcification of costal cartilage, increase of stiffness of rib cage, respiratory muscle weakness, and imbalance of inspiratory and expiratory pressures occur, and in turn, these changes tend to cause more decline of the pulmonary function19,20,21 ) . Therefore, the results of this study are considered to be a phenomenon showing the reason why the pulmonary function declined because the function of pulmonary alveoli, airways and respiratory system were weakened in the aging process.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 However, the use of orthopedic manual therapy techniques focused on the thoracic region has demonstrated benefits to range of motion and pulmonary function. [20][21][22][23][24] In patients with chronic airflow limitation, the effectiveness of manual therapy techniques to improve pulmonary function parameters is controversial. [25][26][27] According to a recent systematic review, however, the addition of manual therapy to an exercise program appears to enhance the benefits obtained for pulmonary function in these patients.…”
Section: Introductionmentioning
confidence: 99%